Elaboración de un manual de procesos de manufacturación para senderos, del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la UA-CAREN de la Universidad Técnica de Cotopaxi (fase ii) - Toaquiza Toaquiza, Luz Myrian (2016)
The research aims to facilitate the understanding and development of the creation of a path, providing basic information and pictures dare each of the signs gave way to step to facilitate the reader. The document is to adapt several reports of other investigations such as manual trails of Argentina in which there is extensive exploration, which guides us in a detailed way as the design, construction, maintenance and load capacity of the trails these are some of the issues detailed in this research work. It is a current document has taken into account changes and trends chord conventional tourism with the times, as the so-called alternative tourism, because today there is a need for new activities that draw attention to tourists in which You should be complemented with products and activities in the natural environment….